Vitamin D can Influence the Dental Implants? - Moreira Neto, Sandro; Dalmaceno, Claudia (Brazilian Journal of Implantology and Health Sciences, 2020)
D Vitamin (calciferol) presents an important role in bone metabolism (turnover) and maintenance of calcium and phosphorus levels in blood. The main source of production is sun-stimulated skin. However, characteristics of modern life, such as fear of dermatological damage and use of protective agents, have hindered/reduced sun exposure. In this way, adequate synthesis of this vitamin is impaired, which can affect negatively the clinical success of dental implants. This study aimed to describe the importance of D vitamin and the effect of its deficiency on systemic health and repercussion in dental implants. An electronic search was made in the Scielo, Pubmed and Scopus databases using the descriptors: “deficiency and vitamin D and dental implants”. 13 articles were selected for review and data analysis. Lack or deficiency of D vitamin promoted different alterations such as mild hypocalcaemia, loss of trabecular bone, and severe bone, muscle, immune and metabolic disorders. In case of suspected D vitamin deficiency, patient should be referred to a physician and nutritionist. The existence of possible hypovitaminosis and indication of appropriate therapeutic approach is very important. The studies in vitro and in animals demonstrate the effects of deficiency or effect of vitamin D supplementation on bone metabolism around dental implants. Already the human studies feature great heterogeneity, no link was found between low serum vitamin D levels with an increased risk of early implant loss. Therefore, further research, including longitudinal clinical investigations and systematic reviews, is necessary to better elucidate mechanisms of D vitamin in processes of bone metabolism and osseointegration supporting dentists, physician and nutritionists when in contact with patients who use or will use dental implants.